Membudayakan Perpustakaan Sebagai Tempat Literasi Seorang Pelajar di SMP Negeri 1 Setia Janji - Kiftya, Meilan; Fathur, Muhammad (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2024)
This research aims to describe the implementation of cultivating the library as a literacy place for students at SMP Negeri 1 Setia Janji. This study used descriptive qualitative method. Sources of data are school principals, teachers, librarians, students, and school committees. The data collection technique uses interview techniques. Data analysis techniques are data reduction, data presentation, and conclusions. The results of the research are that SMP Negeri 1 Setia Janji has optimized literacy culture in the library. This can be proven by the availability of an adequate, comfortable and very quiet library for students to use, and the creation of class madding every month to foster interest in reading and curiosity about the information available. The implementation of a literacy culture can develop a character in a student to be responsible, fond of reading, a character that appreciates achievement, a character of curiosity, a character of hard work, social care, tolerance, respect for friends, a character of great curiosity, creativity, a character that loves peace. and care about the environment. Cultivating literacy is carried out in order to improve self-quality, potential, and develop positive character in students.